Gender differences in job mobility and pay progression in the UK - Silvia Avram; Susan Harkness; Daria Popova (University of Essex, Institute for Social and Economic Research (ISER), 2023)
Understanding disparities in the rates at which men and women's wages grow over the life course is critical to explaining the gender pay gap. Using panel data from 2009 to 2019 for the United Kingdom, we examine how differences in the rates and types of job mobility of men and women - with and without children - influence the evolution of wages. We contrast the rates and wage returns associated with different types of job moves, including moving employer for family reason, moving for wage or career-related reasons, and changing jobs but remaining with the same employer. Despite overall levels of mobility being similar for men and women, we find important differences in the types of mobility they experience, with mothers most likely to switch employers for family related reasons and least likely to move for wage or career reasons, or to change jobs with the same employer. We find that, while job changes with the same employer and career related employer changes have large positive wage returns, changing employers for family related reasons is associated with significant wage losses. Our findings show that differences in the types of mobility experienced by mothers compared to other workers provide an important part of the explanation for their lower wage growth and play a crucial role in explaining the emergence of the motherhood wage gap in the years after birth.
Keywords: 330; job mobility; gender wage gap; wage growth; motherhood